2016
DOI: 10.3928/01477447-20160201-03
|View full text |Cite
|
Sign up to set email alerts
|

Use of the G-guide for Measuring Stem Antetorsion During Total Hip Arthroplasty

Abstract: Implant positioning is one of the critical factors influencing postoperative outcomes in total hip arthroplasty (THA). Several studies have reported that the postoperative antetorsion (AT) measurement for the femoral stem inserted without navigation showed wide variability. The current authors developed a simple instrument, the Gravity-guide (G-guide), for intraoperative assessment of stem AT and adjustment. They evaluated the effectiveness of the G-guide with postoperative computed tomography (CT) examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
(18 reference statements)
0
10
0
Order By: Relevance
“…However, with regard to stem anteversion, there is almost no method for accurately determining the anteversion angle of the stem during surgery apart from computer-assisted navigation. Although the accuracy of stem anteversion using the gravity-guide reported by Fujihara et al is 4.6 ± 4.1, it is necessary to attach the large device to the lower leg, and the procedure is complicated [22]. In addition, it cannot be used with various type of stems, and the accuracy in the OA of the knee on the affected side and in uence of stem placement angle (varus/valgus or exion/extension) is also unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, with regard to stem anteversion, there is almost no method for accurately determining the anteversion angle of the stem during surgery apart from computer-assisted navigation. Although the accuracy of stem anteversion using the gravity-guide reported by Fujihara et al is 4.6 ± 4.1, it is necessary to attach the large device to the lower leg, and the procedure is complicated [22]. In addition, it cannot be used with various type of stems, and the accuracy in the OA of the knee on the affected side and in uence of stem placement angle (varus/valgus or exion/extension) is also unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the accuracy of measurements obtained using a goniometer or navigation systems during THA [12][13][14][15][16] (Table 4). They reported that the mean absolute measurement accuracy ranged from 4.5°-7.3°.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported the optimal positions for the acetabular components, and the accuracy of acetabular component positioning using free-hand techniques, mechanically guided techniques, or navigation systems have also been investigated [8][9][10][11]. Other studies have examined the accuracy of intraoperative measurements of stem anteversion obtained using a goniometer or navigation systems during THA [12][13][14][15][16]. However, only one CTbased navigation study has reported the accuracy of stem positioning during THA [17].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, accurate implantation is very important. In recent years, mechanical intraoperative support devices or navigation systems have been used to place implants accurately [3,4].…”
Section: Introductionmentioning
confidence: 99%